PENGARUH KEAKTIFAN BERORGANISASI DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA 2025 - Nabilah, Luthfiyyah; Fajrini, Fini (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Academic achievement is one of the important indicators of success in the education process. Learning achievement, which reflects the results of learning efforts, can be measured through various parameters, such as the Achievement Index (IP). This IP value is obtained from the evaluation process during the study period, including the assignments given, the results of the mid and final semester exams, class participation, and the level of student activeness in learning. This research is a quantitative study using a Cross Sectional approach. The population in this study were all students of the Faculty of Public Health, Muhammadiyah University of Jakarta who were administrators of organizations, totaling 161 students. The sampling technique is using Total Sampling with a sample size of 161 Respondents. Data analysis methods using Univariate and Bivariate with Chi-Square test at 95% confidence level (α=0.05). The results showed that the variables associated with learning achievement were organizational activity (p=0,004) and learning motivation (p=0,002). Students are expected to maintain a balance between organizational and academic activities so that learning achievement is not neglected, the faculty can provide more support for students who are active in organizations by implementing more flexible academic policies, and further research is recommended to use a larger sample. Prestasi akademik menjadi salah satu indikator penting keberhasilan dalam proses pendidikan. Prestasi belajar, yang mencerminkan hasil usaha belajar, dapat diukur melalui berbagai parameter, seperti Indeks Prestasi (IP). Nilai IP ini diperoleh dari proses evaluasi selama masa studi, mencakup tugas-tugas yang diberikan, hasil ujian tengah dan akhir semester, partisipasi di kelas, serta tingkat keaktifan mahasiswa dalam pembelajaran. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan pendekatan Cross Sectional. Populasi dalam penelitian ini adalah seluruh mahasiswa Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta yang menjadi pengurus organisasi, yakni berjumlah 161 siswa. Teknik pengambilan sampel yaitu menggunakan Total Sampling dengan jumlah sampel sebanyak 161 Responden. Metode analisis data menggunakan Univariat dan Bivariat dengan uji Chi-Square pada tingkat kepercayaan 95% (α=0,05). Hasil penelitian diperoleh bahwa variabel yang berhubungan dengan prestasi belajar adalah keaktifan berorganisasi (p=0,004) dan motivasi belajar (p=0,002). Mahasiswa diharapkan untuk tetap menjaga keseimbangan antara kegiatan organisasi dan akademik agar prestasi belajar tidak terabaikan, fakultas dapat memberikan dukungan lebih bagi mahasiswa yang aktif berorganisasi dengan menerapkan kebijakan akademik yang lebih fleksibel, dan penelitian selanjutnya dianjurkan menggunakan sampel lebih besar.